Development of corn supply chain strategy in East Java based on logistics cost structure and marketing efficiency - Andika Yuli Heryanto; Novita Erma Kristanti; Kuncoro Harto Widodo (AGROINTEK, 2025)
East Java has the highest corn production center, with a percentage of 26.24%. The highest production occurred in 2022, reaching 6,608,822 tons. The market's corn supply instability occurs due to uneven harvest patterns. Price disparities between consumers and farmers occur because many supply chain actors are involved, causing losses to supply chain actors. The impact of the El Nino phenomenon can increase logistics costs, especially in procurement activities. This research aims to develop a supply chain strategy based on an analysis of logistics cost structure, marketing margin, profit margin ratio, and farmer's share. Primary data were gathered through interviews and observations. There were 98 respondents, distributed across three regencies : Kediri, Jember, and Tuban. Calculation of logistics cost structure used the ABC method with descriptive statistical analysis. The supply chain strategy was arranged through FGD with several participants. The results of the logistics cost analysis showed that the most significant proportion of logistics costs for corn supply chain actors is in procurement activities, with a percentage of 63.09% and a total cost of IDR 1,649,304 per kg of corn. Marketing is inefficient because marketing margins and profit margin ratios are not evenly spread across all tiers. The supply chain strategy at the farmer level includes standardizing fertilizer use, choosing the proper fertilization method, and using pesticides in a timely and appropriate dose. Apart from that, there is the purchase of superior corn seeds, using seed planters, and maximizing the number of laborers. The supply chain strategy at the collector trader and large trader tier in transportation activities includes maximizing vehicle loads and creating corn storage areas in each corn production center area